Characteristics of sagittal vertebral alignment in flexion determined by dynamic radiographs of the cervical spine. - Lin R; Tsai K; Chu L; Chang P; Lin, R M; Tsai, K H; Chu, L P; Chang, P Q (Spine (03622436))
Study Design: This study was conducted to depict the change patterns of intervertebral motion of the cervical spine during flexion, upright, and extension positions using dynamic radiographs. Special interest was focused on the flexion position.Objectives: To find reliable criteria for judging the normal intervertebral flexibility based on a survey of the normal population.Methods: The lateral dynamic radiographs of 75 normal subjects were analyzed by digitization and computer calculation. The characteristics of intervertebral positions were investigated using flexion radiographs.Results: From extension to flexion, the angles of intervertebral angular displacement changed from lordosis with different degrees to nearly 0 degrees, which means the adjacent endplates are almost parallel, except at C1-C2; the intervertebral translation changes from slightly retrolisthetic to zero displacement. Using C2-C3 as a baseline to calculate the intervertebral differences of angular displacement and translation in flexion radiographs, nearly all the intervertebral differences of angular displacement were less than 7 degrees, and those of translation were less than 0.06 mm.Conclusions: Qualitative changes from extension to flexion and quantitative values of intervertebral differences in flexion radiographs help define the normal flexibility of the cervical spine more accurately.